African poverty through the lens of labor economics: Earnings & mobility in three countries. - Sandefur, J; Serneels, P; Teal, F (GPRG, 2006)
In this note we make use of embryonic labour market panel surveys of the urban sectors of Ghana and Tanzania, and a longer term survey from Ethiopia, to address some aspects of the determinants of earnings across the wage and self-employed and provide preliminary evidence on transitions across labour market states. We argue that the type of panel data presented here provides insights into the growth process in Africa and directly links to understanding the process of poverty reduction.